Early Gestation Feeding Method Improves Reproductive Performance of Sow - Su, S. P.; Hsia, L. C.; Jantasin, W.; Lee, J. W.; Hsuuw, Y. D. (Tropical Animal Science Journal, 2025)
The relationship between feed intake during early gestation and sows’ reproductive performance is controversial. The purpose of this experiment was to investigate the effects of different feeding strategies during early gestation on reproductive performance in sows. A total of 24 primiparous sows were randomly assigned to one of the following three treatments: Treatment 1: Feed 1.5 kg from mating to day 30 of gestation; Treatment 2: Feed 1.5 kg from mating to day 7, then feed 2.5 kg from days 8 to 30; Treatment 3: Feed 2.5 kg from days 0 to 30. Increased feed intake affected body weight during early gestation. The treatment provided 2.5 kg per day resulted in the highest litter size. While there was no significant difference in litter size between Treatment 2 and Treatment 3, the birth weight and weaning weight of piglets in Treatment 2 seemed better than those in Treatment 3. Increasing feed intake during early gestation (days 0–30) significantly increased litter size. However, Treatment 2, which increased feed intake from days 8 to 30, improved growth performance but did not enhance reproductive performance. In conclusion, high feed intake throughout early gestation significantly increased litter size but also had the potential to increase the number of stillbirths.